DREM2: a facile fabrication strategy for freestanding three dimensional silicon micro- and nanostructures by a modified Bosch etch process. (13th July 2018) - Chang, Bingdong; Jensen, Flemming; Hübner, Jörg; Jansen, Henri
Abstract: Three dimensional (3D) silicon micro- and nanostructures enable novel functionalities and better device performances in various fields. Fabrication of real 3D structures in a larger scale and wider applications has been proven to be limited by the technical difficulties during the fabrication process, which normally requires multiple process steps and techniques. Direct top-down fabrication processes by modifying a plasma etch process have been proposed and studied in previous studies. However, the repeatability, size uniformity and the maximal number of stacked layers were limited. Here we report a facile single run fabrication strategy for three dimensional silicon micro- and nanostructures. A good uniformity of suspended layer thickness has to be achieved and up to 10 stacked layers have been fabricated in a single run without other additional steps or post-process procedures. This is enabled by a modified multiplexed Bosch etch process, so called DREM (deposit, remove, etch, multistep), while the DREM etch is used to transfer the patterns into silicon, an extra isotropic etch creates a complete undercut and thus freestanding structures come into form. This method is easy to program and provides well-controlled etch profiles.